(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Islamic city has its own character that distinguishes it from other urban environments. This is because it followed the Islamic ideology related to building the land. This led to that all cities built during early Islamic ages had followed the same principles in any part of the Islamic world. It is argued that the characteristics of the urban space configuration have a big role in making these cities successful environments. The key aspect in this matter is the distribution of land uses within the urban structure as it is directly associated with people movement and the distribution of their activities. The Friday mosques as the most important components of the Islamic city was located in a way that gave the city its own character. This study supposes that the distribution of the Friday mosques was affected by the way in which the urban space was configured. It aimed to find out to what extent this configuration influenced locating the Friday mosques in the urban fabric. Using space syntax as an analytical technique and the Old Mosul city as a case study, this research analyzed the spatial structure against several spatial characteristics with mosques locations to meet its goal.Â Â